2021
DOI: 10.1111/ane.13530
|View full text |Cite
|
Sign up to set email alerts
|

Ethical issues in stroke thrombolysis revisited

Abstract: Ethical issues in stroke thrombolysis revisitedBack in 1997, a bioethical paper on intravenous thrombolysis in acute ischaemic stroke (IVT), authored by Anthony J. Furlan and George Kanoti, was published. 1 Based on the criteria modified from Schwartz 2 (safety, efficacy, effectiveness, efficiency and outcome), the authors found several ethical problems that were associated with IVT. They can be summarised as a weak proportionality between positive and negative outcomes, and a lack of relation to patient prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The use of thrombolytic in the 3 to 4.5 h time window is still under debate. 3,18,19 The only study designed to specifically evaluate the efficacy of tPA within 3 and 4.5 h after symptom onset (ECASS-III) found benefit (mRS score 0-1 at 90 days) and safety (symptomatic ICH or death) independent to stroke severity. 20 However, only 128 patients with an NIHSS score of 0 to 5 were included in ECASS-III.…”
Section: Discussionmentioning
confidence: 99%
“…The use of thrombolytic in the 3 to 4.5 h time window is still under debate. 3,18,19 The only study designed to specifically evaluate the efficacy of tPA within 3 and 4.5 h after symptom onset (ECASS-III) found benefit (mRS score 0-1 at 90 days) and safety (symptomatic ICH or death) independent to stroke severity. 20 However, only 128 patients with an NIHSS score of 0 to 5 were included in ECASS-III.…”
Section: Discussionmentioning
confidence: 99%
“…Although CCA is considered a naive imputation method, it generally over‐estimates benefit and under‐estimates harm 3 . These findings cast doubt on assumptions made that MOD are missing at random (MAR) and is consistent with prior concerns regarding excess mortality with alteplase treatment 31 …”
Section: Discussionmentioning
confidence: 63%
“…3 These findings cast doubt on assumptions made that MOD are missing at random (MAR) and is consistent with prior concerns regarding excess mortality with alteplase treatment. 31 A major difference between the neuroimaging guidance treatment meta-analysis and the chosen meta-analysis are de-facto exclusions of stroke mimics in the former. Given the marked difference in mortality and likelihood that stroke mimics contribute to survival at 90 days, stroke mimics may be an important source of attrition bias in time-based treatment meta-analyses.…”
Section: Different Methods Of Imputation Incur Different Tradeoffs In...mentioning
confidence: 99%
“…There are at least three objections to this way of reasoning. Non‐significant results are not proof of the null hypothesis; they only show that the examined material does not have sufficient power to prove the research hypothesis 4,5 Even if it could be confirmed that the increased mortality was neutralized between 7 days and 6 months, it would still mean that many patients were deprived of life days. In the Cochrane review of thrombolysis, it is clear that the reduced mortality observed between 7 and 10 days and end of follow‐up, was driven by IST‐3 only 6 .…”
mentioning
confidence: 97%
“…Non-significant results are not proof of the null hypothesis; they only show that the examined material does not have sufficient power to prove the research hypothesis. 4,5 2. Even if it could be confirmed that the increased mortality was neutralized between 7 days and 6 months, it would still mean that many patients were deprived of life days.…”
mentioning
confidence: 99%